Tetramethylpyrazine and paeoniflorin combination (TMP-PF) alleviates atherosclerosis progress by reducing hyperlipemia and inhibiting plaque angiogenesis via the NR4A1/VEGFR2 pathway - Rong Yuan; Qiqi Xin; Weili Shi; Yu Miao; Zhengchuan Zhu; Yahui Yuan; Ying Chen; Xiaoning Chen; Sean Xiao Leng; Keji Chen; Weihong Cong (Food Science and Human Wellness)
Atherosclerosis remains a great threat to human health worldwide. Previous studies found that tetramethylpyrazine (TMP) and paeonif lorin (PF) combination (TMP-PF) exerts anti-atherosclerotic effects in vitro. However, whether TMP-PF improves atherosclerosis in vivo needs further exploration. The present study aims to assess the anti-atherosclerotic properties of TMP-PF in ApoE-/- mice and explore the related molecule mechanisms. Results showed that TMP and high-dose TMP-PF decreased serum triglyceride and low-density lipoprotein cholesterol levels, suppressed vascular endothelial growth factor receptor 2 (VEGFR2) and nuclear receptor subfamily 4 group A member 1 (NR4A1) expression in aortic tissues, inhibited plaque angiogenesis, reduced plaque areas, and alleviated atherosclerosis in ApoE-/- mice. Also, TMP-PF exhibited a better modulation effect than TMP or PF alone. However, NR4A1 agonist abolished the anti-atherosclerotic effects of TMP-PF. In conclusion, TMP-PF was first found to alleviate atherosclerosis progression by reducing hyperlipemia and inhibiting plaque angiogenesis via the NR4A1/VEGFR2 pathway, indicating that TMP-PF had a positive effect on reducing hyperlipemia and attenuating atherosclerosis development.